Reintegration of Returning International Migrants: The Role of Public Programs. - Petschek, Nicholas. (2017)
Abstract: Return and reintegration programs target a variety of migrants and are implemented by a variety of actors, including home country governments. This thesis uses return migration and reintegration theories along with practices from current return and reintegration programs to contextualize the Colombian experience. Because of several novel additions to the Colombian programs-- specifically an emphasis on involving the international community and potentially host countries along with building local capacity instead of simply addressing issues from the top down--the case illuminates a new potential direction for other similar programs in home countries. However, despite these new and promising additions several lessons can be learned from using an embeddedness framework to examine program design and evaluation methods.; Thesis (M.A.)--Tufts University, 2012.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Weiping Wu.; Committee: Katrina Burgess.; Keywords: Urban planning, and International relations.